2005
DOI: 10.3758/cabn.5.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive effects of phobia-related stimuli in animal-fearful individuals

Abstract: Two experiments were conducted to explore neurocognitive effects of phobia-related stimuli. Contingency assessments and event-related potentials (ERPs) were collected from animal-fearful individuals during probabilistic classification learning in diverse motivational-affective contexts. As revealed by ERPs, attentional amplification of cortical sensory processing occurred in response to phobiarelated stimuli. In particular, the posterior selection negativity in the ERPs to phobia-related stimuli had its origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…Most likely, informative cues already triggered an emotion allowing participants to anticipate what they would experience in response to the target. This possibility accords with existing evidence on cued affective responding (Kolassa et al, 2005; Kopp and Altmann, 2005; Miltner et al, 2005; Michalowski et al, 2009, 2014) and on the relation between LPP amplitude and emotion (Yang et al, 2012; Herbert et al, 2013; Langeslag and van Strien, 2013; Sarlo et al, 2013; Galli et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most likely, informative cues already triggered an emotion allowing participants to anticipate what they would experience in response to the target. This possibility accords with existing evidence on cued affective responding (Kolassa et al, 2005; Kopp and Altmann, 2005; Miltner et al, 2005; Michalowski et al, 2009, 2014) and on the relation between LPP amplitude and emotion (Yang et al, 2012; Herbert et al, 2013; Langeslag and van Strien, 2013; Sarlo et al, 2013; Galli et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
“…Correspondingly, ERP studies found that affectively informative cues increase the LPP if they predict an emotional as compared to a neutral stimulus (Kolassa et al, 2005; Kopp and Altmann, 2005; Miltner et al, 2005; Michalowski et al, 2009, 2014). For example, in a study by Michalowski et al (2015), a colored fixation cross informed participants whether an upcoming picture would be neutral, unpleasant, or contained a spider.…”
Section: Introductionmentioning
confidence: 96%
“…Activity in each individual region is summarized in Table 1. 0.0003], with differential activation to phobogenic vs. neutral images absent at follow-up [t(11) = 1.57, P = 0.14]. This pattern suggests that fear-cued enhancements in sensory cortex processing (16,25) may represent a relatively recalcitrant phenomenon that is moderated only after gradual adjustment.…”
Section: Resultsmentioning
confidence: 92%
“…Based on a previous study (Kolassa et al, 2006), it was predicted that the P1 component is enlarged in spider phobics compared to healthy volunteers irrespective of the hedonic valence of the stimulus materials. Subsequently, indexed by the EPN and LPP components (cf., Kopp & Altmann, 2005;Kolassa et al, 2005;Miltner et al, 2005), a fear-specific modulation was expected contrasting the processing of fearful stimuli in spider-fearful and healthy groups. Moreover, presenting other emotional arousing pictures allowed a more refined assessment of fear-specific processing in spider phobics.…”
mentioning
confidence: 91%